2010
DOI: 10.1016/j.jbiomech.2009.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Invariant ankle moment patterns when walking with and without a robotic ankle exoskeleton

Abstract: To guide development of robotic lower limb exoskeletons, it is necessary to understand how humans adapt to powered assistance. The purposes of this study were to quantify joint moments while healthy subjects adapted to a robotic ankle exoskeleton and to determine if the period of motor adaptation is dependent on the magnitude of robotic assistance. The pneumatically-powered ankle exoskeleton provided plantar flexor torque controlled by the wearer's soleus electromyography (EMG). Eleven naïve individuals comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
125
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 21 publications
14
125
2
2
Order By: Relevance
“…The knee moment impulse reduction may stem from an attempt by the participants to prevent the total knee moment from changing in the presence of the external disturbance. This result is consistent with other studies, as humans have been observed to maintain invariant joint moments at both the ankle [25] and hip joints [26] when an external torque from an exoskeleton is applied. This finding has a potential consequence: if the applied joint moment from the AG exceeded the affected knee moment from the ZERO condition, the participant might attempt to maintain total joint kinetics by providing an active extension moment with their quadriceps, so to prevent the total knee flexion moment from increasing.…”
Section: Discussionsupporting
confidence: 93%
“…The knee moment impulse reduction may stem from an attempt by the participants to prevent the total knee moment from changing in the presence of the external disturbance. This result is consistent with other studies, as humans have been observed to maintain invariant joint moments at both the ankle [25] and hip joints [26] when an external torque from an exoskeleton is applied. This finding has a potential consequence: if the applied joint moment from the AG exceeded the affected knee moment from the ZERO condition, the participant might attempt to maintain total joint kinetics by providing an active extension moment with their quadriceps, so to prevent the total knee flexion moment from increasing.…”
Section: Discussionsupporting
confidence: 93%
“…We found that humans significantly reduced soleus recruitment when walking with a powered exoskeleton that acutely increased the gain between either soleus Kao et al 2010a) or gastrocnemius (Kinnaird and Ferris 2009) activation and the resulting plantar flexor torque. This resulted in total (human ϩ exoskeleton) ankle moments that were comparable to unassisted walking (Kao et al 2010a).…”
mentioning
confidence: 85%
“…We have previously employed robotic exoskeletons to investigate human adaptation to acute disruptions of the neuromuscular map of two plantar flexor muscles: soleus and gastrocnemius (Cain et al 2007;Gordon and Ferris 2007;Kao et al 2010a;Kinnaird and Ferris 2009). These two muscles typically display similar activation profiles during gait (Arsenault et al 1986).…”
mentioning
confidence: 99%
“…In order to guide the development of lower limb exoskeletons, some studies (Kao et al, 2010) had, as purpose, the understanding of how humans adapt to powered assistance.…”
Section: D Geonea and D Tarnita: Design And Evaluationmentioning
confidence: 99%